EFFICIENCY OF RESOURCE-USE AND ELASTICITY OF PRODUCTION AMONG CATFISH FARMERS IN IBARAPA, OYO STATE, NIGERIA - AYANBOYE, A. O.; RAFIU, R. A.; MORAWO, B. O.; AKANMU, A. O.; KOLAWOLE, A. S.; FATUROTI, E. O. (Nigerian Journal of Fisheries, 2021)
The productivity level in fish farming has remained low in the aquaculture sector despite its significant role in Nigeria's economy. This is largely due to inadequate knowledge on the optimum use of available resources. This study investigated the resource-use efficiency of catfish fish farmers' production in Ibarapa, Oyo state, Nigeria. Data were obtained from 40 catfish farmers selected by means of purposive random sampling technique through a structured questionnaire. The Cobb-Douglas production function revealed that capital, pond size, fish seed, and feed were significant at P<0.05) but labor was not significant (P>0.05) and was found to be low. This showed that farms were operating at decreasing returns to scale with a value of 0.432 obtained. Resource use efficiency values were -0.158, 0.022, 3.343, 0.898, and -0.002 for fixed input, pond size, fish seed, feed, and labor respectively. This suggests that overutilization is recorded for a fixed input, pond size, feed, and labor with efficiency ratios of less than one, indicating a stage III of catfish production while the fish seed is under- utilized. It was recommended that appropriate training be given to fish farmers in the area that will ensure optimal utilization of the resource.